(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Nostalgia -wishful longing for something removed and attractive- is one of the dominant traits of modern English poetry. It would be too much to assign the reason of the longing for otherworldliness to the devastations of the second world war II, because this kind of longing is found in the romantic poets, also, particularly in Shelley and Keats. Shelley in his lyrical drama “Prometheus Unbound” borrowed the materials of his poems from the Greek legend associated with Prometheus and longed for a world which would be free from suzerainty, oppression and tyranny and where everybody would breathe a sigh of relief and the master passion would be mutual trust, sympathy and love.